Trade and commodification in contemporary world ceramics (Al-Academy, 2023)
The research deals with the global ceramic achievement within the international forums in the past decades. As follows، showing and presenting the aesthetic and intellectual values leading to common constants that establish international artistic studies that achieve the purpose of circulation and marketing of artworks. Contemporary global plastic art has witnessed a number of technical and social transformations and changes at the technical and pragmatic levels under the pressure of the changing and accelerating tide towards technical، cognitive، social and cultural concepts.The second chapter came to the first topic: deliberative and commoditization، and the second topic: the deliberativeness of contemporary global ceramics.Results:_Culture is a deliberative act between the individual and the other، and cultural circulation has a pragmatic system that refers us to commodification_ Contemporary global ceramics has a deliberative system that is linked to the culture of peoples، and it is the one that established the transition to its artistic construction towards being close to or in contact with the act of commodification.The research concluded with the most important references، sources، and a summary of the research in English.